2006
DOI: 10.1038/sj.bjc.6603151
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cytology and human papillomavirus testing in relation to the menstrual cycle

Abstract: Cervical smears prepared around the time of menses have been linked to unsatisfactory specimens and false negative results; however, it is unclear whether liquid-based cytology is similarly affected and data relating date of last menstrual period (LMP) to human papillomavirus (HPV) DNA testing are conflicting. Accordingly, we evaluated liquid-based cytology and HPV test results using Hybrid Capture 2 and PCR by LMP (days 0 -10; 11 -21; 22 -28). We studied 5060 participants in ALTS, the Atypical Squamous Cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Another large study investigating high-risk HPV detection within the menstrual cycle showed a small midcycle increase of HPV detection. 9 However, data on OCP use are not reported and therefore it is difficult to compare this study with our results. A smaller study by our group, in nonusers, found a higher rate of HPV-positive samples in the follicular phase.…”
Section: Discussionmentioning
confidence: 78%
“…Another large study investigating high-risk HPV detection within the menstrual cycle showed a small midcycle increase of HPV detection. 9 However, data on OCP use are not reported and therefore it is difficult to compare this study with our results. A smaller study by our group, in nonusers, found a higher rate of HPV-positive samples in the follicular phase.…”
Section: Discussionmentioning
confidence: 78%
“…Only one other study evaluated HPV viral load, and investigators found a modest increase during midcycle. 4 It is unclear why viral load detection would be higher for specimens collected during this time, but it has been suggested that peak oestrogen levels at midcycle could promote this effect by enhancing HPV viral replication, or by reducing cellular adhesion. 4 In this study, we found no indication that viral load varies with menstrual phase.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether the phase of a woman's menstrual period at the time of cervical sampling has an effect on HPV detection, as previous studies have provided conflicting results. [1][2][3][4][5][6] A recent study exploring the effect of oral contraceptive (OC) use on HPV detection revealed a higher detection rate during the follicular phase among non-users, whereas OC users experienced a higher detection rate during the luteal phase. 7 Using data collected in the Ludwig-McGill cohort study conducted in Brazil, we evaluated the effect of menstrual phase on HPV detection, and attempted to validate previous findings concerning OC use.…”
Section: Introductionmentioning
confidence: 99%
“…The present analysis included 112 HIVpositive and 115 HIV-negative women who had at least three visits during the 3-year follow-up. The aims of the study were: (i) to identify viral infections variably detected in a single cervical swab (Sherman et al, 2006) and (ii) to assess the relationship between HPV genotypes and cytological results. During each visit, cervical cell scrapings were collected with a cytobrush from the ecto-and endocervix of each woman and after spreading of cells on slides (Pap smears), the remaining cells were suspended in 1 ml lysis buffer [10 mM Tris/HCl (pH 7.6), 5 mM EDTA, 150 mM NaCl, 1 % SDS] and stored at 220 uC until analysis.…”
Section: Methodsmentioning
confidence: 99%